Corticolous lichens of beech habitats from the Zacharovanyi Krai National Nature Park: primeval forests versus derivative stands (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Within the territory of the Zacharovanyi Krai National Nature Park, three monitoring plots of 1 ha each were established. These plots revealed 171 species of lichens and 3 species of lichenicolous fungi from 95 genera, 45 families, 22 orders, 9 classes and 2 divisions. In the study plot “Irshava-1”, which is an acidophilous beech primeval forest, 111 species of epiphytic and epixylic lichens as well as 3 species of lichenicolous fungi were found. This plot contained 71 species (41 % of the total number of species) that were not present at the other plots. On the bark of the trunk and branches of the fallen Fagus sylvatica tree, 53 lichen species were recorded and it was the highest number of any of the monitoring plots. In contrast, only 15 species of epiphytic lichens were found in the “Irshava-2” plot, which represents a derived acidophilous beech forest. However, 92 species of lichens were recorded in the “Kuk” plot, which represents mountain beech and maple forests. This plot had 60 species of lichens (34 % of the total number of species) that were not found in the other plots. The species Gyalecta herculina, Lobaria pulmonaria, Melanelixia elegantula and Parmeliella triptophylla, which are included to the Red Data Book, were found in “Irshava-1” and “Kuk” plots. Conclusions: The Irshavka primeval forest site, a UNESCO World Heritage Site, can be considered a reference for acidophilous beech forest habitats in terms of lichen species diversity. The recovery of lichen cover in acidophi-lous beech forest habitats after clear-cutting is very slow. In areas of beech forest (tree age 10–50 years) where clear-cutting has taken place, lichen diversity is 7.5 times lower than in the reference area. The traditional management of the mountain pastures, especially sheep grazing since the beginning of the 19th century, has led to the formation of specific beech forest habitats with a rich epiphytic cover on old trees, featuring significant precence of moderately nitrophilic and heliophilic lichen species.
Keywords: biodiversity, hot-spot plots, indicator species, red data book, Zakarpattia region, Ukraine